Pesticide-Related Hospitalizations Among Children and Teenagers in Texas, 2004–2013. (July 2016) - Trueblood, Amber B.; Shipp, Eva; Han, Daikwon; Ross, Jennifer; Cizmas, Leslie H.
Objective: Acute exposure to pesticides is associated with nausea, headaches, rashes, eye irritation, seizures, and, in severe cases, death. We characterized pesticide-related hospitalizations in Texas among children and teenagers for 2004–2013 to characterize exposures in this population, which is less well understood than pesticide exposure among adults. Methods: We abstracted information on pesticide-related hospitalizations from hospitalization data using pesticide-related International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) codes and E-codes. We calculated the prevalence of pesticide-related hospitalizations among children and teenagers aged ≤19 years for all hospitalizations, unintentional exposures, intentional exposures, pesticide classifications, and illness severity. We also calculated age- and sex-specific prevalence of pesticide-related hospitalizations among children. Results: The prevalence of pesticide-related hospitalizations among children and teenagers was 2.1 per 100, 000 population. The prevalence of pesticide-related hospitalizations per 100, 000 population was 2.7 for boys and 1.5 for girls. The age-specific prevalence per 100, 000 population was 5.3 for children aged 0–4 years, 0.3 for children and teenagers aged 5–14 years, and 2.3 for teenagers aged 15–19 years. Children aged 0–4 years had the highest prevalence of unintentional exposures, whereas teenagers aged 15–19 years had the highest prevalence of intentional exposures. Commonly reported pesticide categories were organophosphates/carbamates, disinfectants, rodenticides, and other pesticides (e.g., pyrethrins, pyrethroids). Of the 158 pesticide-related hospitalizations, most were coded as having minor ( n= 86) or moderate ( n= 40) illness severity. Conclusion: Characterizing the prevalence of pesticide-related hospitalizations among children and teenagers leads to a better understanding of the burden of pesticide exposures, including the type of pesticides used and the severity of potential health effects. This study found differences in the frequency of pesticide-related hospitalizations by sex, age, and intent (e.g., unintentional vs. intentional).